إشراك العراق في النظام التجاري العالمي متعدد الأطراف ( مواجهة التحديات ) (المجلة العراقية للعلوم الاقتصادية, 2018)
This paper is congider as attempt to take view of the most important challenges which facing the Iraqi economy accession to WTO, as observant member now and managed many introductory negotiations meetings. Discovering the possible potentials to facing such challenges is the other target of the paper.The most concern mater is considering WTO accession as sum-zero game, especially to Iraq and other developing countries, when gains of one side equal to losses of other side, in this case there is minimum chance to be the Iraqi economy is the winner side. But all optimists believe that the game is sum-positive game, all sides get gains, which doesn’t proved to all pessimists yet, in spite of all classic and modern trade theories.For that purposes the paper presents expected challenges analysis in the fields preferences, SMCs, trade facilitation, Israel boycott and regional integration, ending with special prospect to face such challenges.